1990
DOI: 10.1007/bf00192461
|View full text |Cite
|
Sign up to set email alerts
|

Reduced antibody response to the repetitive sequence of the Plasmodium falciparum circumsporozoite protein in mice infected with Plasmodium yoelii blood forms

Abstract: The immunogenicity of the carrier-free synthetic peptide, (NANP)40, from the repetitive region of the Plasmodium falciparum circumsporozoite (CS) protein was investigated in genetically responder mice (C57BL/6, H-2b) acutely infected with blood forms of the non-lethal murine malaria parasite, P. yoelii. As compared to non-infected mice, P. yoelii-infected C57BL/6 mice produced significantly lower titers of anti-(NANP)40 IgG antibodies. This decrease in the anti-(NANP)40 antibody response peaked with the peak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Grillot et al [4] reported that mice immunized with synthetic peptide, (NANP) 40 , emulsified with complete Freund's adjuvant also showed suppressed antibody responses to the peptide during P. yoelii malaria infection. In their experiment, however, immunization of the synthetic peptide was carried out only once during infection and the mice were periodically examined for antibody response after that.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grillot et al [4] reported that mice immunized with synthetic peptide, (NANP) 40 , emulsified with complete Freund's adjuvant also showed suppressed antibody responses to the peptide during P. yoelii malaria infection. In their experiment, however, immunization of the synthetic peptide was carried out only once during infection and the mice were periodically examined for antibody response after that.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that the splenic macrophages of the malarious mice were functionally defective as accessory cells in antibody response to horse and sheep erythrocytes [1,11,17,18]. On the other hand, Grillot et al [4] reported that mice immunized with repetitive region of P. falciparum circumsporozoite (CS) protein, (NANP) 40 , also showed suppressed antibody responses to the synthetic peptide during P. yoelii malaria infection. However, the mechanisms responsible for the suppression induced by P. yoelii malaria remain to be determined.…”
mentioning
confidence: 99%